Pengaruh Model Problem Based Learning (PBL) Berbantuan Literasi Digital terhadap Kemampuan Menulis Teks Biografi Siswa Kelas 10 SMK Negeri 1 Merdeka - Resa Restari Br Sembiring (Penerbit Widina, Widina Media Utama, 2025)
This study aims to: (1) examine the biographical text writing ability of class X students of SMK Negeri 1 Merdeka; (2) describe the biographical text writing ability of class X students of SMK Negeri 1 Merdeka through the application of the Problem Based Learning (PBL) Model assisted by digital literacy; and (3) test the effect of the Problem Based Learning (PBL) Model assisted by digital literacy on the biographical text writing ability of class X students of SMK Negeri 1 Merdeka. The research approach used was an experiment with a pre-experimental design in the form of a one group posttest design. The research population included all class X TITL students of SMK Negeri 1 Merdeka, totaling 54 students and divided into two classes. The research sample was determined in one class, namely class X TITL with a total of 24 students. The results of the study showed that before the application of digital literacy, students' biographical text writing ability was in the sufficient category with an average score of 62.04. After the treatment was given, the average score increased to 78.04 and was included in the good category. This increase occurred because students were able to recognize and utilize digital literacy as a means of searching and processing data. The results of the t-test at a significance level of ? = 0.05 with degrees of freedom (df) = 23 showed a t-value of 10.29 and a p-value of 0.00. Because the p-value 0.05, the null hypothesis (H?) is rejected and the alternative hypothesis (H?) is accepted. Thus, it can be concluded that the use of digital literacy has a significant influence on the ability to write biographical texts of class X students of SMK Negeri 1 Merdeka.ABSTRAKPenelitian ini bertujuan untuk: (1) mengkaji kemampuan menulis teks biografi siswa kelas X SMK Negeri 1 Merdeka; (2) mendeskripsikan kemampuan menulis teks biografi siswa kelas X SMK Negeri 1 Merdeka melalui penerapan Model Problem Based Learning (PBL) berbantuan literasi digital; serta (3) menguji pengaruh Model Problem Based Learning (PBL) berbantuan literasi digital terhadap kemampuan menulis teks biografi siswa kelas X SMK Negeri 1 Merdeka. Pendekatan penelitian yang digunakan adalah eksperimen dengan desain pre-eksperimental berupa one group posttest design. Populasi penelitian meliputi seluruh siswa kelas X TITL SMK Negeri 1 Merdeka yang berjumlah 54 siswa dan terbagi ke dalam dua kelas. Sampel penelitian ditetapkan pada satu kelas, yaitu kelas X TITL dengan jumlah 24 siswa. Hasil penelitian menunjukkan bahwa sebelum penerapan literasi digital, kemampuan menulis teks biografi siswa berada pada kategori cukup dengan nilai rata-rata 62,04. Setelah perlakuan diberikan, nilai rata-rata meningkat menjadi 78,04 dan termasuk dalam kategori baik. Peningkatan ini terjadi karena siswa telah mampu mengenal serta memanfaatkan literasi digital sebagai sarana pencarian dan pengolahan data. Hasil uji t pada taraf signifikansi ? = 0,05 dengan derajat kebebasan (df) = 23 menunjukkan nilai thitung sebesar 10,29 dan p-value sebesar 0,00. Karena nilai p-value 0,05, maka hipotesis nol (H?) ditolak dan hipotesis alternatif (H?) diterima. Dengan demikian, dapat disimpulkan bahwa penggunaan literasi digital memberikan pengaruh yang signifikan terhadap kemampuan menulis teks biografi siswa kelas X SMK Negeri 1 Merdeka.